Dr. Lourenço Teixeira — Deep Plane Facelift — Caxias do Sul - Teixeira, Lourenço (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Lourenço Teixeira, practicing in Caxias do Sul, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002962; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; caxias do sul